Complete revascularization improves survival of patients resuscitated after an out-of-hospital cardiac arrest. (2nd May 2022) - Kajana, V; Primi, R; Gentile, FR; Compagnoni, S; Baldi, E; Mandurino Mirizzi, A; Repetto, A; Ferrario, M; Ferlini, M; Marinoni, B; Currao, A; Bendotti, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sudden cardiac death is a major issue in industrialised countries and survival of patients who suffered from an out-of-hospital cardiac arrest (OHCA) remains awfully low. An acute myocardial infarction is the principal cause of OHCA and myocardial revascularisation plays a positive role in survival. In this particular setting little is known about the role of complete versus culprit-only revascularisation on survival. Purpose: The aim of the present study was to assess whether a complete revascularisation could lead to a better one-year survival as compared to culprit-only revascularisation. Methods: All the patients prospectively enrolled in the OHCA registry of the Lombardy region (Lombardia CARe) from January 1, 2015 to May 1, 2021 in the province of Pavia who underwent a coronary angiography at our Polyclinic were enrolled in the study. All the coronary angiographies were retrospectively reviewed by two interventional cardiologists and angiographic features were inserted in the database. Prehospital data and survival were retrieved from the registry according to the Utstein style. Results: We enrolled 239 patients [mean age 63.7±12.4 years; male 79.9%; presenting shockable rhythm 84.1%; acute myocardial infarction at post ROSC ECG 67.9%; ejection fraction 37% (30-45), circulatory support with ECMO 10.9%]. Among the 119 (50%) patients with a multi-vessel disease 82 (69%) received an incomplete revascularisation whereas 37 (31%) were completely revascularised [8 during the first procedure, 29 in a second procedure with a median time after OHCA of 5 (2.5-10) days]. This latter group showed a significantly higher one-year survival (54.9% vs 16.2%, p<0.001). At univariable logistic regression only a shockable presenting rhythm and the presence of a chronic coronary occlusion were found to be significantly associated with the probability of receiving a complete revascularisation [OR 5.1 (95% CI 1.1-22), p=0.03; OR 0.37 (95% CI 0.16-0.85), p=0.02 respectively]. However, at multivariable regression analysis only the presence of a chronic coronary occlusion was confirmed to be significantly associated with the probability of receiving a complete revascularisation [OR 0.36 (95%CI 0.15-0.9), p=0.007]. At Cox multivariable regression model cardiac arrest duration (longer that the median value of 24 min) and a complete revascularisation were shown to be independently associated with the probability of death [HR 3.6 (95%CI 1.9-6.9), p<0.001; HR 0.2 (95%CI 0.1-0.9), p=0.02]. Similarly, cardiac arrest duration, a complete revascularisation and a shockable presenting rhythm were associated with the probability of death or poor neurologic outcome [HR 3.3 (95%CI 1.8-6), p<0.001; HR 0.5 (95%CI 0.3-0.9), p=0.03 and HR 0.2 (95%CI 0.1-0.5), p<0.001]. Conclusions: A complete revascularisation is independently associated with a better one-year survival in patients resuscitated from an out-of-hospital cardiac arrest.